Sense of place, risk perceptions and preparedness of a coastal population at risk (Faro Beach, Portugal): a qualitative content analysis - Domingues, Rita B. (2018)
Faro Beach, a heavily urbanized settlement in Ria Formosa, southern Portugal, is highly vulnerable to coastal hazards, namely beach erosion and overwashes caused by storms, that have resulted in house and road damage on several occasions. Despite the risks, local residents accept to live there. Four semi-structured interviews were conducted to understand residents’ beliefs, risk perceptions and preparedness regarding coastal risks. We used a qualitative content analysis to derive manifest contents from the interviews. Three main themes were identified in the interviews: how residents feel about Faro Beach; how they perceive coastal hazards and risks; and how they deal with those risks. Positive feelings regarding Faro Beach were identified in all residents, reflecting a strong sense of place that includes high levels of place attachment, rooting, sense of community and place identity. Residents’ personal experiences with hazards probably undersized their perceptions regarding the risks that they are exposed to. Their willingness to participate in disaster risk reduction measures seemed associated with behavioral barriers driven by mistrust in authorities and externalization of responsibility. Residents also revealed low levels of preparedness towards coastal hazards, probably due to their low risk perceptions and their perception of threats as distant in time.